Characteristics and association of gender to dental and occlusal anomalies in Malaysian primary school children / Najiyatu Nazihah Zakaria, Saraswathy Devi Sinniah and Annapurny Venkiteswaran - Zakaria, Najiyatu Nazihah; Sinniah, Saraswathy Devi; Venkiteswaran, Annapurny (Faculty of Dentistry, Universiti Teknologi MARA, 2021)
Aim: To describe the distribution and association of dental and occlusal anomalies to gender in children of mixed and early permanent dentition. Methods: It is a cross-sectional study with stratified random sampling based on the main ethnic composition involving 413 subjects aged between 9 and 11 years old enrolled in 7 national primary schools in Sungai Buloh, Selangor. A calibrated operator carried out clinical examinations, and study models were fabricated. All dental and occlusal anomalies were recorded accordingly and were analysed using SPSS version 21.0. Pearson chi-square test was used to determine the gender-based differences for various parameters. Results: The reported dental anomalies were supernumeraries and clinically missing teeth (impacted or hypodontia) with a prevalence of 1.5% and 6.3%, respectively. The occlusal abnormalities were: crowding (54.0%), sagittal discrepancies (overjet; increased, reduced, and reversed overjet: 55.5%), vertical discrepancies (overbite; increased, reduced, and open bite: 37.5%) and transverse discrepancies (unilateral and bilateral posterior crossbite: 5.1%). Gender-based differences were not statistically significant to all reported dental and occlusal anomalies (p>0.05). Conclusions: Children in the mixed and early permanent dentition showed various dental and occlusal anomalies with crowding being the highest anomaly. Gender was not associated with any type of dental or occlusal characteristics in the studied population.